Phytohormones dynamics during flowering initiation in carrots - Samuolienė, Giedrė; Duchovskis, Povilas; Urbonavičiūtė, Akvilė (Acta Biologica Szegediensis, 2005)
This study was aimed on investigation of phytohormones dynamics in carrot (Daucus carota L.) during different flowering initiation stages. Different levels of development were needed for photo- and thermo-induction; tipically 5 and 9 leaves in rosette for the first and second flowering induction stages, respectively. The process of carrot flowering initiation and morphogenesis was studied in a phytotron facility. High-performance liquid chromatography was used for separation of phytohormones. The best rate of development was found during exposure to florally inductive effect with low temperature either a short day or long day photoperiod in carrots with 9 leaves in rosette. Temperature influence had higher effect on phytohormones biosynthesis than differences in photoperiod. Antagonistic as well as stimulatory steps were involved during hormonal action and the balance of these determined the final effect of even a single hormone. The ratio of investigated phytohormones had substantial influence on flowering initiation processes. An increase of gibberellic acid content in evocation stage II and decrease in flower initiation stage determined faster stem elongation and bud formation. Decrease of abscisic acid and increase of gibberellic acid level in evocation stage II could be related with fast flowering induction processes. The highest indol-3 acetic acid concentration in evocation stage II induced the formation of inflorescence axis structures.